The Analysis of Social Values in the Novel Bayanaka Sigrah by Ichamfs14 - Pamungkas, Bayu; Chanafiah, Yayah; Agustina, Emi (Jurnal Korpus, 2025)
The aim of this research is to describe the social events and social values contained in the novel Bayanaka Sigrah. This research is in the form of a qualitative descriptive study. The approach used is literary sociology. The data source for this research is social events and social values in the novel Bayanaka Sigrah by Ichamfs14. Data collection techniques use library research. Data analysis techniques include reading and understanding, creating a synopsis, describing, reviewing/analyzing, and making conclusions. The results of the research show that the social events contained in the Bayanaka Sigrah novel are about sexual relations outside marriage, harassment of female workers, fraternal bonds between humans, self-eradication from poverty and defamation. The social events above have impacts related to social values. The social values in the Bayanaka Sigrah novel include; gender equality, hard work, empathy, sympathy, concern for others, and compassion.